The Effect of Closed House Density Near the Outlet on the Production of Carcass, Non-Carcass, and Abdominal Fat of Finisher Broilers - Widjaya, Nilawati; Wasito, Wasito; Suryanah, Sari; Akhdiat, Tedi; Permana, Hilman; Haroen, Ucop; Widyawati, Susi Dwi (ANIMAL PRODUCTION, 2023)
The purpose of this study was to investigate the closed-house cage density near the outlet that affected the production of carcass, non-carcass, and abdominal fat of finisher phase broilers and to ascertain the number of closed-house cage density that could produce the ideal amount of carcass, non-carcass, and low abdominal fat. The experiment employed a completely randomized design with four treatments: T0 (10 birds per square meter), T1 (12 birds per square meter), T2 (14 birds per square meter), and T3 (16 birds per square meter). It was replicated five times using different numbers of broilers in each replication depending on the cage density. The observed variables were live weight, carcass weight, percentage of carcass, percentage of non-carcass, and percentage of abdominal fat. Data were subjected to analysis of variance and further tested with Duncan's multiple-range test. The study was carried out for 35 days at Farm H. Noto Miharjo in Adiwarno Village, Buayan District, Kebumen Regency, Central Java. The research results showed that the live weight, carcass weight, and carcass percentage were significantly impacted by closed-house cage density at the area near the outlet, although non-carcass percentage and abdominal fat were not significantly impacted. A closed house cage density of 12 birds per square meter at the area near the outlet can provide an optimal production of carcass, non-carcass, and abdominal fat.